Fiqh Learning Worship Based on Demonstrations and Direct Practice: Literature Review on Strategies and Their Impact on Students' Understanding - Faqihuddin, Muhammad; Dartim, Dartim (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The learning of worship fiqh in Islamic educational institutions often faces a gap between the mastery of concepts (harmony, conditions, and legal provisions) and the procedural accuracy of the implementation of worship. This condition emphasizes the importance of a learning strategy that not only targets cognitive achievement, but also builds practice skills and worship habits. This article aims to map practice-based worship fiqh learning strategies at various levels of education and analyze its impact on students' understanding. The research uses a qualitative approach with the type of library research. Secondary data is obtained from relevant scientific literature, then analyzed using content analysis through the stages of in-depth reading, theme coding, categorization, and inter-source synthesis. The results of the review show that practice-based learning strategies tend to follow a tiered pattern of "from knowing, doing, getting used to it". At the MI/SD level, practice is more directed at internalizing values through example, demonstration, media utilization, and rotational practice. At the MTs level, practice is more structured (preparation-implementation-final) and strengthened with guidance and monitoring to extend habituation from the classroom to daily life. Practice-based learning improves students' understanding (cognitive and procedural) and encourages learning engagement, noting the need to strengthen meaning so that practice does not become a routine without appreciation.